Three-Dimensional Organization of Smooth Endoplasmic Reticulum in Hippocampal CA1 Dendrites and Dendritic Spines of the Immature and Mature Rat - Spacek, Josef (J Neurosci, 1997)
Recent studies have shown high levels of calcium in activated dendritic spines, where the smooth endoplasmic reticulum (SER) is likely to be important for regulating calcium. Here, the dimensions and organization of the SER in hippocampal spines and dendrites were measured through serial electron microscopy and three-dimensional analysis. SER of some form was found in 58% of the immature spines and in 48% of the adult spines. Less than 50% of the small spines at either age contained SER, suggesting that other mechanisms, such as cytoplasmic buffers, regulate ion fluxes within their small volumes. In contrast, >80% of the large mushroom spines of the adult had a spine apparatus, an organelle containing stacks of SER and dense-staining plates. Reconstructed SER occupied 0.001–0.022 μm(3), which was only 2–3.5% of the total spine volume; however, the convoluted SER membranes had surface areas of 0.12–2.19 μm(2), which were 12 to 40% of the spine surface area. Coated vesicles and multivesicular bodies occurred in some spines, suggesting local endocytotic activity. Smooth vesicles and tubules of SER were found in continuity with the spine plasma membrane and margins of the postsynaptic density (PSD), respectively, suggesting a role for the SER in the addition and recycling of spine membranes and synapses. The amount of SER in the parent dendrites was proportional to the number of spines and synapses originating along their lengths. These measurements support the hypothesis that the SER regulates the ionic and structural milieu of some, but not all, hippocampal dendritic spines.